Teknologi Internet Sebagai Sumber Belajar Pada Mata Pelajaran Sejarah Di SMAN 14 Padang - Mustiko Budi; Ridho Bayu Yefterson (Jurnal Kronologi, 2023)
Observations of students at SMAN 14 Padang found that students used the internet as a learning resource in history subjects. This makes researchers interested in seeing how high the use of the internet is that students use as a learning resource in history subjects. This research is a quantitative descriptive research that aims to find out the extent of the use of the internet as a learning resource used by students in history subjects. The subjects in the study were 35 students of class XI social studies who were taken as samples/respondents. Data was collected through a questionnaire with 7 indicators along with 17 statement items. Questionnaire data is processed using the help of SPSS in simple terms and Microsoft Excel. The results showed that the availability of the internet as a source of learning history (77.25%), the accuracy of the function of the internet as a source of learning history (80%), the intensity in accessing history learning resources (62.75)%, the facilities used (73.75)%, the internet can accelerate the pace of history learning (85.5)%, the use of the internet through teacher guides and independently 76.75%, types of history learning resources such as Wikipedia (55.71%), blogs (37.14%), scientific journals (32.85%), Online News (38.57%), YouTube (79.28%), Ruang Guru (55%), Zenius (47.14%), Brainly (82.85%), Ebooks (33.57%).